1995
DOI: 10.1088/0305-4470/28/8/026
|View full text |Cite
|
Sign up to set email alerts
|

A pragmatic approach to the problem of the self-adjoint extension of Hamilton operators with the Aharonov-Bohm potential

Abstract: We consider the problem of self-adjoint extension of Hamilton operators for charged quantum particles in the pure Aharonov-Bohm potential (infinitely thin solenoid). We present a pragmatic approach to the problem based on the orthogonalization of the radial solutions for different quantum numbers. Then we discuss a model of a scalar particle with a magnetic moment which allows to explain why the self-adjoint extension contains arbitrary parameters and give a physical interpretation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 17 publications
(27 reference statements)
1
42
0
Order By: Relevance
“…Self-adjoint extensions of the Dirac Hamiltonian in 3 + 1 dimensions were found in [11]. The works [12,13] present an alternative method of treating the Hamiltonian extension problem in 2 + 1 and in 3 + 1 dimensions. It was shown in [14] that in 2 + 1 dimensions only two values of the extension parameter correspond to the presence of the point-like magnetic field at the origin.…”
Section: Introductionmentioning
confidence: 99%
“…Self-adjoint extensions of the Dirac Hamiltonian in 3 + 1 dimensions were found in [11]. The works [12,13] present an alternative method of treating the Hamiltonian extension problem in 2 + 1 and in 3 + 1 dimensions. It was shown in [14] that in 2 + 1 dimensions only two values of the extension parameter correspond to the presence of the point-like magnetic field at the origin.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature it has been already shown that the standard procedure for the self-adjoint extension of the Dirac Hamiltonian gives rise to a one-parameter family of boundary conditions in the background of an Aharonov-Bohm gauge field [55][56][57]. The specific value of the parameter is related to the physical details of the magnetic field distribution inside a more realistic finite radius flux tube (for a more detailed discussion and for specific models with finite radius magnetic flux see [58][59][60][61][62][63][64][65][66][67][68][69]). The idealized model under consideration is a limiting case of the latter.…”
Section: Fermion Condensatementioning
confidence: 99%
“…Our first order of business is to characterize the self-adjoint realizations of the operator in (1.1); for general references on self-adjoint realizations and their applications to physics see, e.g., [2,6,10,16,17,18,32,33,34,35,42,47]. To do so, we first need to determine the maximal domain of ∆:…”
Section: The Maximal Domainmentioning
confidence: 99%
“…Taking logarithms, we see that as |x| → ∞ for x ∈ Υ, we have log F (ix) ∼ c + log(log x − κ) − 1 2 log x + xR + log 1 + 1 8xR + 9 2(8xR) 2 …”
Section: The ζ-Function With Dirichlet Conditions At R = Rmentioning
confidence: 99%